Analisis Penanganan Incoming Cargo Domestik pada PT. Angkasa Pura Logistik Cabang Bandar Udara International Jenderal Ahmad Yani Semarang - Sabrilla Fajariyani; Awan (MES Management Journal, 2024)
Domestic Incoming Cargo Handling is more complex than Domestic Outgoing Cargo Handling. Domestic Incoming Cargo Handling is where domestic goods are unloaded from the plane and then taken to the cargo terminal to be checked one by one by officers and after that they will be taken to the storage warehouse until the customer picks up the goods. the item. However, to pick up these goods there are conditions that must be met, such as bringing an air bill of lading (SMU), an identity card from the customer. However, in the process of handling incoming domestic cargo, there are still obstacles such as unpredictable weather factors which hinder the release of goods, missing quarantine documents and causing officers to replace new quarantine documents. Goods stray to other airports so officers have to create a new air bill of lading number or (SMU). However, in the process of handling incoming domestic cargo, there are still obstacles such as unpredictable weather factors which hinder the release of goods, missing quarantine documents and causing officers to replace new quarantine documents. Goods stray to other airports so officers have to create a new air bill of lading number or (SMU). occur during the handling process. incoming domestic cargo. This research uses qualitative research. The methods for collecting data in this research are observation, interviews, and finally documentation. The aim of the research is to find out how incoming domestic cargo is handled by operational officers and logistics staff and to find out what obstacles are faced by operational officers and logistics staff and the solutions taken by operational officers and logistics staff if problems occur during the handling process. incoming domestic cargo Based on the data obtained regarding the handling of incoming domestic cargo, the process of handling incoming domestic cargo carried out by operational officers and logistics staff is in accordance with the standard operational procedures (SOP) that apply at PT. Angkasa Pura Logistik, the obstacles faced by officers such as bad weather, lost documents, officers are looking for solutions by speeding up the process of handling goods and replacing lost documents with new ones.